PENGEMBANGAN PEMASARAN KOPI GALUNGGUNG MENGGUNAKAN SISTEM E-COMMERCE - Dona Setia Umbara; Missi Hikmatyar (Universitas Galuh Ciamis, 2020)
The traditional door to door marketing process has become a problem in the distribution of galunggung coffee. Then there needs to be a breakthrough by local stakeholders or entrepreneurs who work closely with farmers in the right marketing system in the distribution of Galunggung coffee. The specific purpose of this research is to expand the marketing of the Galunggung coffee business by developing an online system in the form of E-commerce. The stages of this research include a needs analysis that is preparing all needs related to the research to be conducted. The next stage is the design which includes the design of conventional marketing systems and the design of e-commerce marketing systems. Based on the results of marketing the product on social media, 1,121 people saw parentas product advertisements, and 98% of accounts that did not follow a coffee parentas account. So, marketing coffee products includes an unknown account that has an interest in coffee. there is the result of the age range that sees product advertisements on social media. Ages 24-34 have more interest in coffee after age 18-24 who have an interest in coffee and aged 35-44 have little interest in coffee. So to do better marketing in the age range 24-34.